In the shadow of the state: Think tanks and foreign policy in Latin America - Merke, Mario Federico (2015)
This paper analyzes the role of think tanks as members of civil society in Latin America. Our goal is to present an initial conceptualization and measurement of the role think tanks play in the foreign policy sub-subsystem. We focus on three of the most influential think tanks in the region: CARI (Argentina), CEBRI (Brazil), and COMEXI (Mexico). This paper suggests that the state's characteristics and the character of its civil society determine the type and strength of its think tanks. This paper also considers the challenges that think tanks face in Argentina, Brazil, and Mexico more generally by comparing each chosen think tank's board, public activities, presence in local media and social media, and publications. We conclude that there have yet to be significant incentives and resources available for thinks tanks in Argentina, Brazil, and Mexico to grow and, thus, Latin American think tanks' activities typically follow their governments' agendas.